Endocrine disrupting chemicals: Impact on human health, wildlife and the environment. (March 2019) - Encarnação, Telma; Pais, Alberto ACC; Campos, Maria G; Burrows, Hugh D
Endocrine disrupting chemicals are a group of pollutants that can affect the endocrine system and lead to diseases and dysfunctions across the lifespan of organisms. They are omnipresent. They are in the air we breathe, in the food we eat and in the water we drink. They can be found in our everyday lives through personal care products, household cleaning products, furniture and in children's toys. Every year, hundreds of new chemicals are produced and released onto the market without being tested, and they reach our bodies through everyday products. Permanent exposure to those chemicals may intensify or even become the main cause for the development of diseases such as type 2 diabetes, obesity, cardiovascular diseases and certain types of cancer. In recent years, legislation and regulations have been implemented, which aim to control the release of potentially adverse endocrine disrupting chemicals, often invoking the precautionary principle. The objective of this review is to provide an overview of research on environmental aspects of endocrine disrupting chemicals and their effects on human health, based on evidence from animal and human studies. Emphasis is given to three ubiquitous and persistent groups of chemicals, polychlorinated biphenyls, polybrominated diphenyl ethers and organochlorine pesticides, and on two non-persistent, but ubiquitous, bisphenol A and phthalates. Some selected historical cases are also presented and successful cases of regulation and legislation described. These led to a decrease in exposure and consequent minimization of the effects of these compounds. Recommendations from experts on this field, World Health Organization, scientific reports and from the Endocrine Society are included.